The Role of Adult Education Centers in Syrian Refugees’ Integration Process - Esen Altunay; Serap Karabulut (İnsan & Toplum)
The aim of this study is to reveal the views of administrators and instructors regarding the role adult education centers (AECs) have in the process of integrating Syrian refugees and to present relevant suggestions. This qualitative study has employed a phenomenological design, obtained the data using a semi-structured interview form. The study group of the research consists of administrators and instructors working at AECs in Izmir, Turkey between 2019-2020 and were identified using criterion sampling, a purposive sampling method. As a result of the research, the participants were revealed to have most commonly emphasized language learning under the theme of Syrian refugee adults’ social needs. Among the problems regarding the integration process of the Syrian refugees enrolled in the AECs, absenteeism and economic inadequacy came to the fore under the theme of problems regarding instructees. In terms of the AECs’ contributions to the adaptation process, their contributions to language learning, social adaptation, and establishing communication and relationships were emphasized under the theme of social skills development. According to the research results, states should develop certain policies to produce permanent solutions regarding Syrian refugees’ education and provide financial assistance regarding the problem of refugees’ economic inadequacy; AECs should also strengthen their collaborations with other institutions.